AUDIOGRAM PADA PASIEN OMSK DI POLIKLINIK THT RSUP SANGLAH PADA TAHUN 2011-2012 - Monica Yusilina Mutiara; Sari Wulan Dwi Sutanegara; Wayan Sucipta (DiscoverSys Inc., 2016)
Chronic Suppurative Otitis Media (CSOM) is a chronic infection in the middle ear that can disturb the function of hearing. Impaired the function of hearing which can be caused by CSOM is deafness, ears ringing (tinnitus), pain in the ears (otalgia) and discharge from ears (ottorhea). The examination that workable to test the function of hearing is audiometry examination. Audiometry examination is examination which aims to know degress of deafness and kind of deafness. Examination conducted using instrument audiometer. The purpose of this research is to know classification from deafness and the degree of deafness in people with CSOM in Department of ENT in RSUP Sanglah. The Method of this research is descriptive method using cross sectional design and retrospective data taken from Department of ENT in RSUP Sanglah denpasar. The result showed that the type of deaf conductive was the highest type hearing impairments (73,7%). From 28 people who suffering CSOM with deafness conductive, 20 people having moderate deafness degree (71,4%).